Effects of various antihypertensive therapy strategies on the circadian blood pressure profile, hemodynamics, and endothelial function in adolescents with essential arterial hypertension - I. V. Logacheva; E. A. Gunicheva (Российский кардиологический журнал, 2013)
Aim. To assess the effect of graduated physical exercise and extended release indapamide on the main parameters of circadian blood pressure (BP) profile, hemodynamics, and endothelial function in adolescents with Stage I essential arterial hypertension (EAH). Material and methods. The study included 114 adolescent boys with EHA (mean age 16,6±0,12 years) and 27 healthy boys. All EAH patients were divided into three groups. Group I (n=37) included adolescents with labile EAH, according to the 24-hour BP monitoring results. These participants were administered graduated aerobic physical exercise (GAPE). Groups II and III included patients with stable EAH. Group II (n=41) received indapamide retard (Arifon Retard,Servier,France; 1,5 mg once a day, in the morning). Group III (n=36) received the combination of GAPE and indapamide retard. The therapy duration was 6 months. All participants underwent 24-hour BP monitoring, echocardiography, veloergometry (VEM), assessment of endothelial function, and measurement of endothelin-1 levels. Results. In adolescents with Stage I EAH, both labile and stable variants of hypertension were confirmed by the 24-hour BP monitoring data. GAPE improved circadian BP profile, endothelial function, and hemodynamic parameters in patients with labile EAH. In stable EAH, indapamide retard demonstrated a rapid and consistent BP normalisation and improvement in endothelial function, VEM parameters, and endothelin-1 levels. In high-risk patients with EAH, the antihypertensive effect of the combination of GAPE and indapamide retard was comparable to that of indapamide monotherapy. Conclusion. Graduated physical exercise could be used in patients with labile EAH. In adolescents with stable EAH, indapamide retard (as monotherapy and in combination with GAPE) is both effective and safe in normalising circadian BP profile and delivering cardioprotective and vasoprotective effects.